Adolescent girls' experiences of urban dance programmes: a qualitative analysis of Flemish initiatives targeting disadvantaged youth. Issue 1 (2nd January 2017) - Schaillée, Hebe; Theeboom, Marc; Skille, Eivind
Abstract: A study on urban dance initiatives for disadvantaged girls in Flanders (Belgium) was set up, as there is little insight into the underlying social mechanisms that allow developmental benefits to occur for this group. A fieldwork approach, including observations at three dance sites and interviews with 25 participants, resulted in four main findings. First, the access to the programmes is a necessary but not a sufficient condition to foster developmental outcomes. Second, the participants described benefits across four main areas including sport-related skills, positive identity, social competencies and positive values. Third, there are various social mechanisms through which significant others, including adult staff and peers, can have an impact on participating youth's perceived benefits. Identified mechanisms include observational learning, participants' perceptions of coaches' autonomy supportive behaviours, a caring climate and a motivational climate. Fourth, inherent characteristics of urban dance provide a context for facilitating an autonomy supportive coaching climate. This study adds to existing literature in the way it connects sport-related characteristics with young people's opportunities for positive youth development.